Molecular Characterization of a Novel Family of Trypanosoma cruzi Surface Membrane Proteins (TcSMP) Involved in Mammalian Host Cell Invasion. - Nadini Oliveira Martins; Renata Torres de Souza; Esteban Mauricio Cordero; Danielle Cortez Maldonado; Cristian Cortez; Marjorie Mendes Marini; Eden Ramalho Ferreira; Ethel Bayer-Santos; Igor Correia de Almeida; Nobuko Yoshida; José Franco da Silveira (Public Library of Science (PLoS), 2015)
The surface coat of Trypanosoma cruzi is predominantly composed of glycosylphosphatidylinositol-anchored proteins, which have been extensively characterized. However, very little is known about less abundant surface proteins and their role in host-parasite interactions.Here, we described a novel family of T. cruzi surface membrane proteins (TcSMP), which are conserved among different T. cruzi lineages and have orthologs in other Trypanosoma species. TcSMP genes are densely clustered within the genome, suggesting that they could have originated by tandem gene duplication. Several lines of evidence indicate that TcSMP is a membrane-spanning protein located at the cellular surface and is released into the extracellular milieu. TcSMP exhibited the key elements typical of surface proteins (N-terminal signal peptide or signal anchor) and a C-terminal hydrophobic sequence predicted to be a trans-membrane domain. Immunofluorescence of live parasites showed that anti-TcSMP antibodies clearly labeled the surface of all T. cruzi developmental forms. TcSMP peptides previously found in a membrane-enriched fraction were identified by proteomic analysis in membrane vesicles as well as in soluble forms in the T. cruzi secretome. TcSMP proteins were also located intracellularly likely associated with membrane-bound structures. We demonstrated that TcSMP proteins were capable of inhibiting metacyclic trypomastigote entry into host cells. TcSMP bound to mammalian cells and triggered Ca2+ signaling and lysosome exocytosis, events that are required for parasitophorous vacuole biogenesis. The effects of TcSMP were of lower magnitude compared to gp82, the major adhesion protein of metacyclic trypomastigotes, suggesting that TcSMP may play an auxiliary role in host cell invasion.We hypothesized that the productive interaction of T. cruzi with host cells that effectively results in internalization may depend on diverse adhesion molecules. In the metacyclic forms, the signaling induced by TcSMP may be additive to that triggered by the major surface molecule gp82, further increasing the host cell responses required for infection.